Estudio de factibilidad para la creación de un centro de desarrollo comunitario de la ciudadela La Salud cantón Quevedo año 2015 - Cedeño Mendoza, Nancy Cecibel (2015)
In the canton Quevedo, ciudadela Health a large index indifference when it relates to personal growth and community development denotes the lack of education of the population, limits access to an important part of the population, by yourself aims to create a Community Development Center aims to foster the right conditions for good living promoting the capabilities and skills of the population living in the Citadel Health, provide good conditions and opportunities for culture, learning, participation, recreation and productive and educational projects for all, with an equal projection. In this community setting a visionary activity working together with the community and public institutions in terms of social growth it is proposed. It arises this research create a positive impact on the Citadel's Health as a pilot project with a view to a general development. Community Development Centers offer the possibility of a constant free learning for all, looking for equity and local development. The project has a cost of $ 434,016.64 which will be covered 100% by the Municipality of Quevedo canton, the goal of the Community Development Centre it is to enhance human capabilities through concrete actions in harmony with our historical, cultural and human features . Generating activities promote the exchange of knowledge and wisdom. Provide adequate space for the community overcoming educational programs that enhance their prospects in families.